'Ma Face Vanille': White rappers, 'Black Music', and race in France. (1st November 2014) - Bretillon, Chong J.
If the meanings of 'Frenchness' are highly contested in French culture, then the meanings of whiteness are even more so: France's ideology of inclusion explicitly rejects racial identifications in favour of the universal notion of 'Frenchness'. However, whiteness tends to operate as a signifier of Frenchness, and both colonialism and immigration policies have played a crucial role in the consolidation of this identity. These debates are enriched by the consideration of French popular culture, especially hip hop, a black American cultural import. This article demonstrates how scholarship has largely glossed over the question of whiteness in hip hop, and has thus ignored how white rappers negotiate racial privilege while expressing solidarity with their black and Arabe counterparts. The first part of the article provides an overview of discourses surrounding racial authenticity in both American and global hip hop, to show how French rappers adapted the American racial binary to the multicultural French context. The article then draws upon scholarship in the emerging field of whiteness studies in France to locate white rappers' anti-racist stances within the current structure of French racial politics, arguing that texts and images by some white rap groups give valence to their minority status in hip hop, as a technique to position themselves outside the privilege they are presumed to enjoy as white French people.Dans la culture française, la signifiance des notions de 'Francité' et de 'blanchité' est souvent contestée. En France, l'idéologie de l'intégration rejette toute forme d'identification raciale en faveur de l'universalisme français. Pourtant, la blanchité a tendance à impliquer la Francité et le colonialisme ainsi que la politique de l'immigration qui ont joué des rôles importants dans la consolidation de cette identité. En outre, ce débat autour du concept de blanchité est enrichi par la culture populaire ; voire le hip hop, importé de la forme culturelle noire américaine, s'effectue à cause de l'influence de celui-ci. Cet article démontre que les recherches jusqu'à présent ont pour la plupart ignoré la question de la blanchité dans le hip hop. Également, ils n'ont pas tenu compte de comment les rappeurs blancs négocient leur privilège racial en même temps qu'ils expriment la solidarité avec leurs pairs des rappeurs Noirs et Maghrébins. La première partie de cet article résume les discours au sujet de l'authenticité raciale dans le hip hop américain et mondial pour éclairer comment les rappeurs français ont adapté la binarité raciale américaine au contexte multiculturel français. Ensuite, l'on situera les positions anti-racistes des rappeurs blancs dans la structure actuelle de la politique raciale en France, en affirmant que les textes et les images adoptés par certains rappeurs impliquent leur statut minoritaire dans le domaine du hip hop français--une technique utilisée pour se situer en dehors du statut privilégié--l'on présume qu'ils bénéficient en tant que Blancs.